The Virulence Factor LLO of Listeria monocytogenes Can Hamper Biofilm Formation and Indirectly Suppress Phage-Lytic Effect - Banhong Liu; Mei Bai; Wuxiang Tu; Yanbin Shen; Jingxin Liu; Zhenquan Yang; Hongduo Bao; Qingli Dong; Yangtai Liu; Ran Wang; Hui Zhang; Liangbing Hu (Foods)
Listeria monocytogenes is a life-threatening bacterial foodborne pathogen that can persist in food-processing facilities for years. Although phages can control L. monocytogenes during food production, phage-resistant bacterial subpopulations can regrow in phage-treated environments. In this study, an L. monocytogenes hly defective strain, NJ05-Δhly, was produced, which considerably regulated the interactions between L. monocytogenes and phages. Specifically, we observed a 76.92-fold decrease in the efficiency of plating of the defective strain following infection with the Listeria phage vB-LmoM-NJ05. The lytic effect was notably diminished at multiplicities of infection of 1 and 10. Furthermore, the inactivation of LLO impaired biofilm formation, which was completely suppressed and eliminated following treatment with 108 PFU/mL of phage. Additionally, phages protected cells from mitochondrial membrane damage and the accumulation of mitochondrial reactive oxygen species induced by L. monocytogenes invasion. Transcriptomic analysis confirmed these findings, revealing the significant downregulation of genes associated with phage sensitivity, pathogenicity, biofilm formation, and motility in L. monocytogenes. These results underscore the vital role of LLO in regulating the pathogenicity, phage susceptibility, and biofilm formation of L. monocytogenes. These observations highlight the important role of virulence factors in phage applications and provide insights into the potential use of phages for developing biosanitizers.